1998
DOI: 10.1027/0227-5910.19.4.154
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in Sudanese Women

Abstract: A literature review indicated that suicidal behavior in Sudan was very infrequent. However, an assessment of suicidal ideation in two Sudanese groups of women demonstrated high levels, particularly in women in a displaced-persons area. In addition, the recent establishment of a Befrienders International volunteer service allowed anecdotal evidence of substantial suicidal behavior to be collated. These findings highlight the need for further professional and volunteer assistance with continuing evaluation and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…5,10,12,16,24,26 However, many studies from several regions of Africa, including overlapping regions of the previous studies, have reported a much higher proportion of women committing suicide suggesting that women may be at higher risk based on local factors. 6,8,9,11,19 Seventy nine percent of our study group committed suicide by using agricultural pesticides (e.g., Termik, organophosphates). Although officially licensed for restricted use on the tea and coffee estates prominent in the Southern Region, Termik is readily available and sold cheaply on the black market.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,10,12,16,24,26 However, many studies from several regions of Africa, including overlapping regions of the previous studies, have reported a much higher proportion of women committing suicide suggesting that women may be at higher risk based on local factors. 6,8,9,11,19 Seventy nine percent of our study group committed suicide by using agricultural pesticides (e.g., Termik, organophosphates). Although officially licensed for restricted use on the tea and coffee estates prominent in the Southern Region, Termik is readily available and sold cheaply on the black market.…”
Section: Discussionmentioning
confidence: 99%
“…1 The range of data from Africa regarding suicide, attempted suicide, and parasuicide from both the clinical and forensic arenas includes many excellent studies; yet, there remains a great need for centralized collection and processing of mortality statistics, including suicide, across the continent. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Published forensic data (i.e., mortality studies) from the late 1970s for the African continent indicate suicides constitute 6.3-7.4% of autopsies. 5,17 Studies from the Centers for Disease Control and Prevention as recent as 1990 found the suicide rate to be lowest in Sub-Saharan Africa (3.4 per 100,000) compared to the rest of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted globally demonstrate a varying trend. Some researchers propose that deliberate self harm has female predilection [16][17][18][19][20][21][22][23][24][25][26][27][28][29] , whereas others proposes view contrary to this. [30][31][32] Several other studies found self-harm to be gender neutral.…”
Section: Discussionmentioning
confidence: 99%
“…I Egypt (Okasha 1981) og Sudan (Goldney et al 1998) er høy forekomst av selvmordstanker ikke reflektert i høye selvmordsrater. Dette kan muligens forstås dithen at selv om det finnes suicidale personer i muslimske samfunn, skjer det ikke så ofte selvmord der siden religionen så sterkt fordømmer det.…”
Section: Islamunclassified